(untitled) - Shelly, Gary B.; Gary B. Shelly; Thomas J. Cashman; Misty E. Vermaat (Boston, Mass., 2008)
Get ready to learn about today's digital world with Essential Introduction to Computers. This concise text provides a visually-engaging, introduction to the most current information on computers and technology. Students will gain an understanding of the essential computer concepts they need to know to help them be successful in today's computing world
Keywords: Computer science; Internet; Computers